A case–control study of caesarean delivery on maternal request: who and why?. (1st September 2016) - Lerner-Geva, Liat; Glasser, Saralee; Levitan, Gila; Boyko, Valentina; Golan, Abraham; Beloosesky, Ron; Lunenfeld, Eitan; Many, Ariel; Samueloff, Arnon; Schiff, Eyal; Shoham, Ann; Fisher, Menachem; et al.
Abstract: Objective : The current study aimed to evaluate the profile of women who are most likely to undergo caesarean delivery on maternal request (CDMR) and clarify their reasons for this decision. Methods : For this multicentre case–control study, data were collected from 429 women who underwent CDMR and 429 matched controls who delivered vaginally from June, 2008 through February, 2009. Participants were interviewed by telephone regarding sociodemographic variables, health and lifestyle. Results : CDMR predictors were as follows: increasing age (OR = 1.09/year; 95%CI: 1.05–1.14), family status (unmarried without a steady partner versus married – OR = 3.60; 95%CI: 1.08–11.97), decreasing level of religiosity (secular versus ultra-orthodox – OR = 11.82; 95%CI: 3.75–37.21), and never having engaged, or ceasing sports activity during pregnancy (OR = 1.79; 95%CI: 1.09–2.91 and 2.38; 95%CI: 1.28–4.43, respectively). Above average income reduced the probability of CDMR (OR = 0.56; 95%CI: 0.33–0.94). The most frequent reasons for choosing CDMR were concern for pain (21.9%), concern for their own or baby's health (20.4% and 16.5%, respectively) and emotional aspects (10.0%). Conclusions : Older, unmarried and/or secular women had increased probability of CDMR. Addressing specific concerns regarding vaginal delivery may provide the basis for a patient-oriented intervention for preventing unnecessary surgery.